Discussions on rail in urban areas and rail history - Aydin, Gokce; Dzhaleva-Chonkova, Anna (ELSEVIER SCI LTD, 2013)
This paper includes discussions on rail in urban areas and railway history. More specifically commonly used terms and definitions for rail services, policy and practice in urban areas are discussed followed by an overview of railway developments around the world. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Rail transport; Urban areas; History; Discussions; Facts; Business & Economics; Transportation